Quality management: tools and methods for improvement - Gitlow, Howard S. (Burr Ridge, IL : Irwin, 1995)
Rev. edition of: Tools and methods for the improvement of quality/ Howard Gitlow...=et. al.= 1989
Includes appendices , references, and index.
Keywords: Quality Management -- Statistical methods